2021
DOI: 10.3390/sports9110153
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Term Effects of Attentional Focus Strategies on Muscular Strength: A Meta-Analysis

Abstract: This review aimed to perform a meta-analysis examining the following: (a) acute effects of adopting an internal focus vs. external focus of attention on muscular strength; and (b) long-term effects of adopting an internal focus vs. external focus of attention during resistance training on gains in muscular strength. We searched through five databases to find eligible studies. Random-effects meta-analyses of standardized mean differences were conducted to analyze the data. Ten studies were included. In the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(48 reference statements)
1
10
1
Order By: Relevance
“…In one study, training with an external focus of attention increased 1RM strength in the squat and deadlift more than training with an internal focus of attention (13% vs. 9%) [ 31 ]. This finding aligns with the data reported in a recent meta-analysis on the topic [ 32 ]. However, the benefits of external focus should not be generalized to muscular hypertrophy, as one study reported that increases in elbow flexor thickness favoured training with an internal focus of attention [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In one study, training with an external focus of attention increased 1RM strength in the squat and deadlift more than training with an internal focus of attention (13% vs. 9%) [ 31 ]. This finding aligns with the data reported in a recent meta-analysis on the topic [ 32 ]. However, the benefits of external focus should not be generalized to muscular hypertrophy, as one study reported that increases in elbow flexor thickness favoured training with an internal focus of attention [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…The Flanker task which was used in the current study measures executive function that enable an individual to focus attention [ 36 ]. Since attentional focus is already reported to moderate acute muscle performance [ 32 , 33 ], decrements in bench press endurance performance during high and moderate hypoxia may be associated with equivalent impairment in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…As the severity of hypoxia increases, the level of deoxygenation increases. Moreover, two recent meta-analyses reported that attention, a parameter of complex cognitive processes, moderates acute muscular endurance [ 32 ] and strength [ 33 ] performance. However, currently there are no studies that have investigated CF before and after resistance exercise during hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…As for upper- and lower-body muscular strength, both the HST and the FRSTS results observed in the EF group highlighted significant improvements after the 6-week training intervention. There is evidence that a short-term period (i.e., six weeks) [ 50 ] of an external cue intervention is sufficient to provide positive effects on maximal handgrip strength, isometric mid-high pull, squat and deadlift tests as compared to an intervention with an internal focus [ 51 , 52 , 53 ]. With this in mind, a resistance training program could be beneficial when dealing with obesity because when muscular strength is normalized to body mass, obese patients are weaker than their normal-weight counterparts.…”
Section: Discussionmentioning
confidence: 99%